Timing and genotype distribution of symptomatic and asymptomatic sapovirus infections and re-infections in a Nicaraguan birth cohort. (April 2023) - González, Fredman; Diez-Valcarce, Marta; Reyes, Yaoska; Vielot, Nadja A.; Toval-Ruíz, Christian; Gutiérrez, Lester; Zepeda, Omar; Cuadra, Edwing Centeno; Blandón, Patricia; Browne, Hannah; Bowman, Natalie M.; Vílchez, Samuel; et al.
Abstract: Objectives: To characterize the timing and genotype distribution of symptomatic and asymptomatic sapovirus infections and re-infections in a Nicaraguan birth cohort. Methods: Infants ( N = 444) were enrolled at 10–14 days of life and observed weekly until 2 years of age. Stool samples were collected for each acute gastroenteritis (AGE) episode, and routine stool samples were collected monthly. Stool samples were tested for sapovirus using RT-qPCR, and positive samples were genotyped. Results: A total of 348 children completed 2 years of AGE weekly surveillance; 93 (26.7%) of them experienced sapovirus AGE. Most infections occurred after 5 months of age and mainly during the second year of life (62.4%, 58/93) and early in the rainy season. Sapovirus screening in all stools from a subset of 67 children who consistently provided samples showed sapovirus infections in 91 of 330 (27.6%) AGE episodes and in 39 of 1350 (2.9%) routine stools. In this subset, the median age at the first sapovirus AGE was 11.2 months (95% CI, 9.3–15.9 months); 38 of 67 (57%) children experienced re-infections, 19 symptomatic and 19 asymptomatic. On average, sapovirus re-infections were reported 7.2 months after symptomatic and 5.3 months after asymptomatic infections. Genogroup GI (64%, 69/108) was the most common detected. Sapovirus GI.1 was more frequently detected in AGE stool samples than in routine stool samples (47.2%, 43/91 vs. 25.6%, 10/39; p 0.005), and re-infection with the same genotype was uncommon. Discussion: The first sapovirus infections occurred at approximately 11 months of age, whereas the median time to symptomatic re-infection was 7.2 months. Re-infections with the same sapovirus genotype were rare during 2 years of life suggesting genotype-specific protection after natural infection.